(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article analyzed the phraseological units representing the concept of food from the point of view of linguoculturalism, to clarify their semantics, to identify, describe and classify the concepts related to people’s culture, values, customs, traditions, and social relations, and on this basis to determine the linguistic value of the paremiological units with the concept of food.